MECHANICAL PROPERTIES OF PALM KERNEL SHELL CONCRETE IN COMPARISON WITH PERIWINKLE SHELL CONCRETE (Malaysian Journal of Civil Engineering, 2018)
Comparative analysis of mechanical properties of palm kernel shell concrete with periwinkle shell concrete is presented in the paper. The binder and fine aggregate were Ordinary Portland cement and river sand, respectively, while potable water was used for mixing and curing. The constituent materials were batched by weight. Concrete mix ratio was 1:2:4 and water/cement ratio was 0.5. Three groups of concrete mixes containing different coarse aggregates were tested: 100% palm kernel shells, 100% periwinkle shells, and 100% granite as control. Tests were carried out for bulk density and compressive strength of the concrete cubes at 7, 14, 21, and 28 days curing, respectively. The results revealed that for all curing ages, palm kernel shell concrete had lower bulk density and lower compressive strength than periwinkle shell concrete. The bulk density and compressive strength of the 28-day palm kernel shell concrete were 1840 kg/m3 and 14.02 N/mm2, respectively, those of periwinkle shell concrete were 1936 kg/m3 and 16.90 N/mm2, while those of granite concrete were 2496 kg/m3 and 25.95 N/mm2, respectively. Both palm kernel shell concrete and periwinkle shell concrete satisfied the bulk density and compressive strength requirements for lightweight aggregate concrete.